PEMERIKSAAN DAN PUTUSAN TANPA KEHADIRAN TERDAKWA TINDAK PIDANA KORUPSI DALAM PENGADILAN KAITANNYA DENGAN HAK ASASI TERDAKWA - I Nyoman Agus Trisnadiasa; Ni Komang Ratih Kumala Dewi (Faculty of Law, Mahasaraswati University, Denpasar, 2020)
The perspective of legal development, examination and decision without the presence of the defendant in a corruption case are regulated in the provisions of Article 38 paragraph (1) of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, but there are norms that are contrary to the principle of the presence of the accused before the accused the trial is governed by the provisions of Article 189 paragraph (1) of the Criminal Procedure Code. These conflicting norms create a dilemma for choosing practices in absentia that eliminate the rights of the accused or protect the rights of the suspect. The research method used in this study is normative research.Article 38 paragraph (1) of the Law on the Elimination of Criminal Acts of Corruption can be applied provided that a legal summon is first carried out. and the procedure does not violate the defendant's human rights, bearing in mind the principle of derogation which, as in the application of Article 29 of the UDHR, Article 4 paragraph (2) of ICCOR and Article 28J of the 1945 Constitution, rights which can be postponed Keywords: , ,